2019
DOI: 10.15252/embr.201847528
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21‐mediated proteasomal degradation of SAMHD1 regulates its antiviral activity

Abstract: SAMHD1 possesses multiple functions, but whether cellular factors regulate SAMHD1 expression or its function remains not well characterized. Here, by investigating why cultured RD and HEK293T cells show different sensitivity to enterovirus 71 (EV71) infection, we demonstrate that SAMHD1 is a restriction factor for EV71. Importantly, we identify TRIM21, an E3 ubiquitin ligase, as a key regulator of SAMHD1, which specifically interacts and degrades SAMHD1 through the proteasomal pathway. However, TRIM21 has no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 80 publications
(169 reference statements)
0
51
0
Order By: Relevance
“…HCMV infection promotes degradation of SAMHD1 at late stages through the Cullin-RING-E3 ligase complexes 56 . Enterovirus 71 infection increases TRIM21 (an E3 ubiquitin ligase) expression, and TRIM21 directly interacts and degrades SAMHD1 through the proteasomal pathway 25 . On the contrary, HBV-encoded proteins such as hepatitis B virus-X (HBx) benefits virus replication by directly or indirectly degrading multiple cellular restriction factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCMV infection promotes degradation of SAMHD1 at late stages through the Cullin-RING-E3 ligase complexes 56 . Enterovirus 71 infection increases TRIM21 (an E3 ubiquitin ligase) expression, and TRIM21 directly interacts and degrades SAMHD1 through the proteasomal pathway 25 . On the contrary, HBV-encoded proteins such as hepatitis B virus-X (HBx) benefits virus replication by directly or indirectly degrading multiple cellular restriction factors.…”
Section: Discussionmentioning
confidence: 99%
“…The dNTPase activity requires homo-tetramerization of the SAMHD1 protein 23 . Several post-translational modifications, including phosphorylation 24 and ubiquitination 25 , have been reported to be critical for SAMHD1 function. Our group has previously demonstrated that cyclin E2-CDK2 mediates SAMHD1 phosphorylation to abrogate its restriction of HBV replication 26 .…”
Section: Introductionmentioning
confidence: 99%
“…SAMHD1, an effector of innate immunity, can restrict most retroviruses (such as HIV-1) and several DNA viruses (including HBV) by depleting the intracellular pool of dNTPs (Ballana & Esté, 2015). Several post-translational modifications, including phosphorylation (White et al , 2013, 1) and ubiquitination (Li et al , 2019b) have been reported to be critical for SAMHD1 function. Herein, we identified Ser93 as a key O-GlcNAcylation site on SAMHD1 using LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the dNTPase function of SAMHD1 is regulated in several ways as mentioned above. In dividing cells, SAMHD1 has been identified to directly interact with the cyclin A2/CDK complex [12,13,16,70,71], CtIP [55,72], SKP2 [13,14], PP2A-B55α [10], cyclin L2 [73], TRIM21 [74], and various proteins involved in nuclear import [48,54]. Direct binding partners of SAMHD1 in non-cycling cells are still unknown.…”
Section: Samhd1 Protein Contains An Nls and Is Expressed In A Varietymentioning
confidence: 99%